PERAN LATUPATI SEBAGAI LEMBAGA HUKUM ADAT DALAM PENYELESAIAN KONFLIK ANTAR NEGERI DI KECAMATAN LEIHITU PROPINSI MALUKU - Jacoba Sahalessy (SASI, 2011)
Sense of security, order and peace is a basic requirement in the life of a people a very close relationship with law enforcement process. Process of law enforcement in the area of customary law community unit as in the countries of the Moluccas should be understood as a unit which can’t be separated from their culture. Role of Institutions Latupati be one of the institution of customary law (adat institution) which is a cultural identity of indigenous people in Maluku in the resolution of conflicts between countries. Awareness of the legal sistem in fact is at the core of the culture of a community. For those reasons, the existence of latupati institutions need to be maintained and enhanced as an instrument of social control of society, so that the future of this institution is able to contribute to process of law, especially in sub Leihitu.